PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA DENGAN KEPEMIMPINAN SEBAGAI INTERVENING PADA BINDA KEPRI - Putro, Agung Cahyo; Santoso, Cahyo Budi; Oktavianti (LPPM Universitas Ibnu Sina, 2021)
This study aims to analyze the influence of organizational culture and motivation on performance in Binda Kepri. This research uses path analysis method and hypothesis testing and hypothesis testing using partial t test and simultaneous F test. The results showed (1) Organizational Culture had a positive and significant effect on the leadership of Binda Kepri (2) Motivation had a positive and significant effect on the leadership of Binda Kepri. (3) Organizational culture has a negative and insignificant effect on the performance of Binda Kepri (4) Motivation has a negative and insignificant effect on the performance of Binda Kepri. (5) Leadership has a positive and insignificant effect on Binda Kepri's performance (6) Organizational culture has a negative and insignificant effect on Binda Kepri's performance with leadership as mediation (7) Motivation has a negative and insignificant effect on Binda Kepri's performance with leadership as mediation.